The Routledge handbook of institutions and planning in action. - (:unkn) unknown (Routledge, 2018)
'The Routledge Handbook of Institutions and Planning in Action' contains a selection of 25 chapters prepared by specialized international scholars of urban planning and urban studies focusing on the question of how institutional innovation occurs in practices of action. The contributors share expertise on institutional innovation and philosophical pragmatism. They discuss the different facets of these two conceptual frameworks and explore the alternative combinations through which they can be approached. The relevance of these conceptual lines of thought will be exemplified in exploring the contemporary practices of sustainable (climate-proof) urban transition. The aim of the handbook is to give a boost to the turn of institutional analysis in the context of action in changing cities. Both philosophical pragmatism and institutional innovation rest on wide international uses in social sciences and planning studies, and may be considered as complementary for many reasons. However, the combination of these different approaches is all but evident and creates a number of dilemmas.
Keywords: Stadtplanung; Planungstheorie; Planungspraxis; Institution; Innovation; Aktionsraum; Theorie; Fallstudie; Governance; Steuerung; Institutionenforschung; Planungsebene; Local Governance; Stadtsystem; Planungsethik; Handbuch